Results of the implementation of a pharmacogenomics platform based on NGS technologies. Combining clinical and research approaches - Ramudo-Cela, Luis; Busto-Fernández, Fernando; Outeda-Macías, María; Antolín, Silvia; Calvo-Martínez, Lourdes; Martín-Herranz, Isabel (Farmacia hospitalaria : organo oficial de expresion cientifica de la Sociedad Espanola de Farmacia Hospitalaria, 2021)
As more genes are incorporated into pharmacogenomic care  processes and more importance is given to rare variants, the use of targeted  capture sequencing panels has been proposed as a very efficient alternative  due to their affordability, high throughput, and deep coverage, all of them  characteristics of high-quality next-generation sequencing data. The purpose of  this study is to describe the prevalence of clinically actionable  pharmacogenetic variants previously described in the scientific literature, as  well as that of new variants identified by next-generation sequencing  technologies, and to evaluate the drugs potentially affected by such variants. A panel of 18 clinically actionable pharmacogenomics-related genes  was evaluated in 41 subjects diagnosed with breast cancer undergoing  neoadjuvant treatment. The prevalence of previously descri- bed clinically  actionable variants as well as of phenotypes classified according to current  interpretation standards was studied. The pharmacological treatments  potentially affected by the identified variants were also evaluated. An  estimation was made of the prevalence of not previously described, possibly  deleterious, variants selected using bioinformatics criteria. All subjects carried clinically actionable variants, with a mean of 4.02  genes affected by each variant per individual. VKORC1, CYP4F2, CYP2C19,  CYP2D6 and CYP2B6 were the most polymorphic genes and were present with  actionable phenotypes in more than 50% of patients; 15-50% had actionable  phonotypes in UGT1A1, SLCO1B1, CYP2C9 and TPMT and 2-15% in HLA-B,  CYP3A5, HLA-A and DPYD. No actionable variants were identified in RYR1,  CACNA1S, G6PD, F5 and NUDT15. These variants had the potential to affect  response to 84% of the drugs described in the leading pharmacogenetic  guidelines. Possibly deleterious variants not previously described accounted for  11.4% of all clinically actionable variants and were present in 12.2% of  patients. The results obtained show a high prevalence of clinically actionable variants, both common, i.e., previously described in the  literature, and rare, i.e., not previously studied with conventional technological  approaches. The latter are candidates for a more exhaustive  molecular and/or clinical characterization.